Proactive contracting in finnish ppp projects - Tieva, Antti; Junnonen, Juha-Matti (International Journal of Strategic Property Management, 2009)
Public‐private‐partnership projects are long term, complex and very challenging contractual arrangements and relationships. They bring new roles for public sector and also for private sector in terms of construction and services. This paper will go through some features of the Finnish PPPs. Proactive law focuses in practical views as regards contract law and contractual issues. The main target is to prevent problems instead of confronting them. This paper will clarify what proactive law is about in terms of contract law and contracting especially in PPPs. For instance, 20–40 years’ partnership relation with PPPs brings up also dozens of different risks into the picture. This paper will discuss the risks and risk management in terms of proactive law and after that, focus on PPPs in Finland.First Publish Online: 18 Oct 2010